Strategic labor market management : comparative analysis of Nordic countries and Russian Federation regions - Kamaleev, Rafael (2022)
The labor potential of society as a whole is the direct engine of progress, and the engine of countries. Effective strategic labor market management should be aimed at increasing labor productivity and gross domestic product in order to maintain life support systems at the proper level for the population. This research includes evaluation of hourly labor productivity for five Nordic countries (Denmark, Finland, Iceland Norway and Sweden) and six Russian Federation subjects (Yamalo-Nenets Autonomous Okrug, Republic of Tatarstan, Tver Oblast, Oryol Oblast, Karachay-Cherkess Republic, Republic of North Ossetia – Alania) during 2006-2020. Analysis showed that there is a huge difference between Russian regions and Nordic countries. Moreover, correlation and regression analysis of the influence of factors on labor productivity showed that investments in fixed assets in Nordic countries have more influence on labor productivity than in Russian regions. Furthermore, Cobb-Douglas Production Function for Norway, Finland, the Yamalo-Nenets Autonomous Okrug and the Republic of Tatarstan for 2006-2020 is designed. Additionally, recommendations for improving the labor market management system at the regional level are developed.